Cognitive Characteristics Of Using Ethnographic Materials In Pedagogy - Aytkulova Guljavxar Shekerbayevna, (European International Journal of Pedagogics, 2026)
The integration of ethnographic materials into pedagogical practice has gained increasing attention in contemporary education due to its potential to enhance learners’ cognitive development, cultural awareness, and critical thinking skills. Ethnographic materials—such as traditions, rituals, folklore, oral histories, and everyday cultural practices—serve not only as sources of knowledge but also as powerful cognitive tools that connect learners’ personal experiences with academic content. This article explores the cognitive characteristics of using ethnographic materials in pedagogy, focusing on how such materials influence perception, memory, thinking, comprehension, and meaning-making processes. The study analyzes theoretical foundations, cognitive mechanisms, pedagogical benefits, and challenges associated with ethnographic approaches in education. The findings suggest that ethnographic materials significantly contribute to deeper learning, contextual understanding, and the development of higher-order cognitive skills when effectively integrated into teaching and learning processes.